(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Characterizing an area of knowledge involves examining documents that help to understand different historical events. In Behavior Analysis, there is a subarea called “Teaching Programming”, responsible for intervening in needs related to the teaching-learning process, originating from works produced in Brazil from the 1960s onwards. Considering this, the objective of this work was to characterize part of the knowledge construction process in this subarea, analyzing the annals of two Brazilian scientific societies in which some of the firsts works were presented. For this purpose, 155 studies were examined in order to identify institutions, departments, authors, regions, and Brazilian states of origin of the works. Terms used, concepts, and other contents present in the collected material were also identified. Therefore, in this work, events that preceded the systematization of Teaching Programming and which can be considered its precursors are presented.